Магнiтнi властивостi квантових кiлець при врахуваннi спiн-орбiтальної та електрон-електронної взаємодiї - Bauzha, O. S. (Publishing house "Academperiodika", 2018)
The separate and combined influences of the spin-orbit and electron-electron interactions on the electron magnetization in quantum rings have been studied theoretically on the basis of the spin-density-functional theory and the Kohn–Sham equation used for the calculation of electron states in two-dimensional parabolic quantum rings containing from two to six electrons. The magnetization of electrons in a quantum ring is calculated at zero temperature. The revealedabrupt changes in the ring magnetization are associated with the crossing of electron states that occurs if the spin-orbit and/or electron-electron interactions are taken into consideration.